1981
DOI: 10.2307/3053225
|View full text |Cite
|
Sign up to set email alerts
|

Human Information Processing and Adjudication: Trial by Heuristics

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and Law and Society Association are collaborating with JSTOR to digitize, preserve and extend access to Law &Society Review. This article addresses the role of quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(85 citation statements)
references
References 65 publications
4
79
2
Order By: Relevance
“…Arkes, 1989;Saks and Kidd, 1980). Anchoring, a bias found in numerous settings, also occurs in civil liability cases when the plaintiff requests a specific amount of compensation or when causal evidence influences compensation judgments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arkes, 1989;Saks and Kidd, 1980). Anchoring, a bias found in numerous settings, also occurs in civil liability cases when the plaintiff requests a specific amount of compensation or when causal evidence influences compensation judgments.…”
Section: Discussionmentioning
confidence: 99%
“…As jurors have to consider a great deal of information in making these judgments, they are likely to rely on cognitive heuristics (Arkes, 1989;Saks and Kidd, 1980), as people commonly do in performing complex cognitive tasks (Bodenhausen and Lichtenstein, 1987). These heuristics often result in systematic biases, such as anchoring (Kahneman and Tversky, 1974).…”
Section: Juror Decision Makingmentioning
confidence: 99%
“…Concern has been expressed regarding the presentation of complex scientific testimony (see, e.g., Cooper, Bennett, & Sukel, 1996) and statistical evidence to juries because such scientific evidence ostensibly would have an exaggerated impact (see, e.g., State v. Boyd, 1983, in which the court barred presentation of population frequency statistics used to analyze blood test results because it anticipated the potential for the jury to be unduly influenced and thus cause unfair prejudice against the defendant). Alternatively, empirical evidence demonstrating systematic biases in human decision-making has suggested that jurors may be more likely to undervalue, rather than attach exaggerated value to, statistical data (Saks & Kidd, 1980). More recently, Smith, Penrod, Otto, and Park (1996) demonstrated that mock jurors generally tended to underuse, rather than overuse, probabilistic evidence.…”
Section: Clinically Versus Statistically Based Testimonymentioning
confidence: 99%
“…People have the tendency to allow individual preferences, expectations, and experiences to influ ence the decision making process (Colwell, 2005). Cognitive heuristics are mental shortcuts often used when a person has to make a difficult decision (Saks & Kidd, 1981). Common heuristics used in court situations include the representative heuristic and availability heuristic (Colwell, 2005).…”
Section: Heuristics In the Court Roommentioning
confidence: 99%